1986
DOI: 10.1530/jrf.0.0760537
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the testosterone to dihydrotestosterone ratio in the epididymis and vas deferens of adult mice

Abstract: The concentrations of testosterone and dihydrotestosterone (DHT) were measured in the testis and in different segments of the epididymis and vas deferens of adult mice. There were marked regional variations in the concentrations of testosterone and DHT from the testis to the caudal part of the vas deferens. In the testis, testosterone was the predominant androgen (364 +/- 90 ng/g) while DHT was weakly represented (8 +/- 2 ng/g). Qualitative and quantitative changes occurred in epididymis: DHT was the main ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 2 publications
1
8
1
Order By: Relevance
“…The epididymis receives rete testis fluid that has 10-to 12-fold higher androgen concentrations than normal serum (Pujol et al, 1976). Luminal and tissular androgen concentration in the caput region is also higher than in the cauda epididymis (Turner et al, 1984;Jean-Faucher et al, 1986). In the present study, bilateral orchidectomy and testosterone replacement in castrated rats were used to determine whether the steady state of mAChR mRNA is under androgen control.…”
Section: Discussionmentioning
confidence: 91%
“…The epididymis receives rete testis fluid that has 10-to 12-fold higher androgen concentrations than normal serum (Pujol et al, 1976). Luminal and tissular androgen concentration in the caput region is also higher than in the cauda epididymis (Turner et al, 1984;Jean-Faucher et al, 1986). In the present study, bilateral orchidectomy and testosterone replacement in castrated rats were used to determine whether the steady state of mAChR mRNA is under androgen control.…”
Section: Discussionmentioning
confidence: 91%
“…4B). The tissue androgen level is higher in the caput epididymis than in the corpus or cauda epididymis [15,38]; thus, apoptotic cells showed in the caput epididymis rather than in the corpus and cauda epididymis following efferent duct ligation. These results may suggest that UCH-L1 and UCH-L3 have reciprocal functions in the caput epididymis fol-lowing apoptotic stress induced by androgen withdrawal, as was shown with cryptorchid stress [25].…”
Section: Discussionmentioning
confidence: 93%
“…However, we also conducted studies on castrated males and observed that glomerular volumes increased in castrated as in intact males, but that this increase in volume was not associated with the development of injury in castrated rats. This persistent increase in Vg with age in castrated males was unexpected since the androgens promote kidney growth (31,32). However, the renotrophic action of testosterone appears to be specific for tubular elements in rats with two kidneys (33) although androgens do contribute to the glomerular hypertrophy that occurs after reduction of renal mass (34).…”
Section: Resultsmentioning
confidence: 99%
“…This sex difference is clinically relevant since the rate of progression towards end stage renal failure in autosomal dominant polycystic kidney disease is significantly slower in women vs men (25). Men are at increased risk to develop end stage renal disease secondary to diabetes and hypertensive complications (26,27) and long It has been suggested that hypertrophy of the glomerular tuft provides a separate risk factor for development of glomerular injury by increased intramural tension (29)(30)(31). In the present study we measured glomerular volumes and observed an increase in volume in intact male rats from 8-12 mo of age, which preceeded the development of the injury.…”
Section: Resultsmentioning
confidence: 99%